IDENTIFIKASI FAKTOR PENYEBAB PERILAKU MENGKONSUMSI MINUMAN BERALKOHOL PADA ATLET SOFTBALL UNIVERSITAS “X” KOTA SEMARANG - Shafira Amalia; Besar Tirto Husodo; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
One kind of sport which is growing now is softball. This is proven by more softball clubs established in some cities in Indonesia, and also clubs in Universities. There are so many tournament that followed by the club makes all the athletes must trained more diligently with heavy training program. It can triggered physical and mental stress. The preferred way to reduce stress is with alcohol consuming. The purpose of this study is to indentify what factors that triggered alcohol consuming by University X Semarang’s softball athletes. The type of research is qualitative research with in-depth interview. The population studied are 8 subject who are member of University X softball team and 4 triangulation subject which is the coach of the team and another member of University X softball team who did not consume alcohol. The result of this study showed that some factors that triggered alcohol consumption by softball athletes are beliefs about the outcome of alcohol consuming can reduce stress, positive result evaluation from alcohol consuming, positive attitude toward alcohol consuming, positive normative believe from surrounding environment such as friend, senior, and coach, motivation gained from itself and also the surrounding environment, positive subjective norms, and behavioral intention that support subjects to consume the alcohol. In this study found that the invitation to consume alcohol from team friends, senior, and friends from another team become an encouragement for subjects to consume alcohol. Alcohol consumption behavior is formed by repetitive activity until it becomes a habit.